Identification of novel DPP–IV inhibitory peptides from Atlantic salmon (Salmo salar) skin. (July 2020) - Jin, Ritian; Teng, Xiangyu; Shang, Jiaqi; Wang, Dangfeng; Liu, Ning
Graphical abstract: Highlights: Peptides in salmon skin collagen were released by trypsin effectively. DPP–IV enzyme activity was inhibited by salmon skin collagen trypsin hydrolyzate. IC50 value of novel DPP–IV inhibitory peptide LDKVFR was 0.1 ± 0.03 mg/mL. LDKVFR bound to DPP–IV through hydrogen bonds and hydrophobic interactions. Abstract: The aim of this study was to identify dipeptidyl peptidase IV (DPP-IV) inhibitory peptides from salmon skin collagen hydrolysate, and to evaluate the possible inhibition mechanism of DPP-IV and peptide. Salmon skin collagen was hydrolyzed by pepsin, trypsin, papain, or Alcalase 2.4 L, separately. Trypsin hydrolysate (10 mg/mL) showed the highest inhibitory activity of 66.12 ± 0.68%. The hydrolysate was separated into three fractions by ultrafiltration, and the inhibitory IC50 of M1 (molecular weight <3 kDa) was 1.54 ± 0.06 mg/mL. M1 was separated by gel chromatography and RP-HPLC; A10 was the highest inhibitory fraction in the 12 fractions, i.e., IC50 was 0.79 ± 0.13 mg/mL. A novel peptide LDKVFR with the IC50 value of 0.1 ± 0.03 mg/mL (128.71 μM) was identified from A10. Molecular docking revealed that six hydrogen bonds and eight hydrophobic interactions between LDKVFR and DPP-IV were contributed to DPP-IV inhibition.